2018
DOI: 10.1016/j.nmni.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

First description of a cefixime- and ciprofloxacin-resistant Neisseria gonorrhoeae isolate with mutations in key antimicrobial susceptibility–determining genes from the country of Georgia

Abstract: Antimicrobial resistance in Neisseria gonorrhoeae is a global health problem. Enhanced international collaborative surveillance and disease control are needed to reduce the global burden of this important pathogen. Currently the antimicrobial resistance properties and molecular mechanisms of multidrug-resistant N. gonorrhoeae in the Republic of Georgia represent a significant knowledge gap. Here we report the isolation of a strain of N. gonorrhoeae exhibiting resistance to cefixime and ciprofloxacin with reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…We identified a single published case report from Georgia in 2018 which presented resistance to cefixime and ciprofloxacin identified in a urethral specimen of a 23-year-old heterosexual man [ 20 ]. Data from Ukraine, reported to GASP, were also included in two publications by Boiko et al [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified a single published case report from Georgia in 2018 which presented resistance to cefixime and ciprofloxacin identified in a urethral specimen of a 23-year-old heterosexual man [ 20 ]. Data from Ukraine, reported to GASP, were also included in two publications by Boiko et al [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The number of countries included in this assessment which participate in the WHO GASP is small as was the availability of published data on AMR in gonorrhoea. It is encouraging that four of these countries reported that there was no resistance to ceftriaxone in 2015 and 2016, although it is noteworthy that a high level of cefixime resistance was found in Belarus and of cefixime-resistant isolates were detected in Kyrgyzstan [ 35 ] and Georgia [ 20 ]. Resistance to ceftriaxone of less than 1% is reported in published literature from Russia [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation